Pengaruh Posisi Duduk dengan Keluhan Nyeri Punggung Bawah pada Penjahit di Tasikmalaya - Zira Afrizeina Kurnia; Tursina, Alya; Perdana, Rizki (Bandung Conference Series: Medical Science, 2024)
Abstract. The Global Burden of Disease (GBD) shows that around 1,71 billion people experienced musculoskeletal disorders in 2019. Diseases caused by work in West Java province continue to increase. Many musculoskeletal disorders arise due to physical factors and poor ergonomics, such as lower back pain. This study aims to analyze the effect of sitting position on complaints of lower back pain among tailors in Tasikmalaya. This research is a cross sectional study conducted at CV Buana Ar-Rahni Tasikmalaya. The research sample came from data taken from interview data in the form of the Oswestry Low Back Pain Disability Questionnaire and body posture assessments of workers were seen using the ovako working sheet assessment on 55 female seamstresses at CV Buana Ar-Rahni. Interview and observation data include age characteristics, educational history, length of work, duration of sewing, complaints of back pain, and ergonomic sitting position. Data were analyzed using bivariate tests and ChiSquare and Lemeshow statistical tests were carried out. Characteristics of all respondents experiencing lower back pain. There were 25 respondents (45,4%) who suffered from mild disabilities. The results of the analysis of the relationship between sitting position and complaints of lower back pain obtained a p value of 0,02 (< 0,05) which shows that there is a significant relationship between sitting position while working and complaints of pain in the lower back among tailors at CV Buana Ar-Rahni. Lower back pain and musculoskeletal pain that occur can be prevented by good sitting positions and ergonomics that are usually used by workers. Abstrak. Global Burden of Disease (GBD) menunjukan ada sekitar 1,71 miliar orang yang mengalami gangguan muskuloskeletal pada tahun 2019. Penyakit yang disebabkan pekerjaan di provinsi Jawa Barat terus mengalami kenaikan. Mayoritas gangguan muskuloskeletal muncul disebabkan faktor fisik dan posisi ergonomi yang kurang baik seperti nyeri punggung bawah. Penelitian ini bertujuan untuk menganalisis pengaruh posisi duduk dengan keluhan nyeri punggung bawah pada penjahit di Tasikmalaya. Penelitian ini merupakan penelitian cross sectional yang dilakukan di CV Buana Ar-Rahni Tasikmalaya. Sampel penelitian berasal dari data yang diambil dari data wawancara berupa kuisioner Oswestry Low Back Pain Disability Quistionare dan penilaian postur tubuh pada pekerja dilihat menggunakan ovako working sheet assessment pada 55 penjahit perempuan di CV Buana Ar-Rahni. Data wawancara dan observasi berupa karakteristik usia, riwayat pendidikan, lama kerja, durasi menjahit, keluhan nyeri punggung, dan posisi duduk ergonomis. Data dianalisis dengan uji bivariat serta dilakukan uji statistik chi-square dan lemeshow. Karakteristik seluruh responden mengalami nyeri punggung bawah. Pekerja yang mengalami disabilitas ringan berjumlah 25 responden (45,4%). Hasil analisis hubungan antara posisi duduk dengan keluhan nyeri punggung bawah didapatkan nilai p sebesar 0,02 (< 0,05) yang menunjukkan terdapat hubungan yang signifikan antara posisi duduk saat bekerja dan keluhan nyeri pada bagian punggung bawah pada penjahit di CV Buana Ar-Rahni. Nyeri punggung bawah dan nyeri muskuloskeletal yang terjadi dapat dicegah oleh posisi duduk yang baik dan ergonomi yang dibiasakan oleh pekerja.